The Influence of Transactional Leadership, Work Motivation, and Job Satisfaction on Employee Performance - Febryana, Aulina; Subiyanto, Didik; Lysander, Mohammad Ahyar Syafwan (LifeSciFi, 2025)
Employee performance is crucial for service quality and competitiveness in the hospitality industry, yet many hotels still face challenges in optimizing it. This study aims to examine the influence of transactional leadership, work motivation, and job satisfaction on the performance of employees. The research adopted a quantitative approach using the census method on all 49 permanent employees as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The results reveal that work motivation and job satisfaction have positive and significant effects on employee performance, whereas transactional leadership shows no significant effect. Work motivation is the most dominant factor, followed by job satisfaction. These findings imply that internal factors such as employee enthusiasm and contentment with the work environment are more influential than a leadership style that relies heavily on rewards and punishments in small-scale hotel settings. Hotel management is recommended to prioritize programs that strengthen employee motivation and satisfaction through fair compensation, recognition, career development, and supportive work atmosphere, while reducing over-reliance on rigid transactional mechanisms. This approach is expected to enhance overall employee performance and guest satisfaction in the long term.